A tale of two syn-rifts: New age information and depositional environment interpretation for the North Falkland Basin syn-rift and implications for the rifting of Gondwana - Rory J. Sutton; Gayle E. Plenderleith; Thomas J.H. Dodd; Lorraine P. Field; Ian L. Millar; Dave J. McCarthy; Thomas A. Randles (Gondwana Research, 2026)

Relative abundance indices for critically endangered oceanic whitetip sharks (Carcharhinus longimanus) derived from pelagic Baited Remote Underwater Video Stations (pBRUVS) - Candace Y. A. Fields; John K. Carlson; Yodelix Melendez; Jack J. Morris; Yannis P. Papastamatiou; Sara N. Schoen; Demian D. Chapman (Marine Biology, 2026)

Mass timber wall splice connection using glued-in rods: Design methodology, implementation, and shake-table testing in a six-story building - Steven Kontra; Andre R. Barbosa; Arijit Sinha; Steve Pryor; Reid B. Zimmerman; Barbara Simpson; John W. van de Lindt; Shiling Pei; Gustavo A. Araújo R.; Morgan McBain; Ludovica Pieroni; Prashanna Mishra; et al. (Engineering Structures, 2026)

Conservation genomics of Pecos pupfish ( Cyprinodon pecosensis ) - Elizabeth P. Dolan; Andrew T. Fields; Megan G. Bean; Robyn R. Doege; Joanna L. Hatt; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2026)
The Pecos pupfish, Cyprinodon pecosensis , is an imperilled freshwater fish found in arid regions of Texas and New Mexico (USA). The species faces multiple challenges to persistence including reductions in suitable habitat, water shortages, as well as hybridization and competition with an introduced congener (sheepshead minnow, C. variegatus ). As part of the current management strategy, refuge populations, seeded with non‐introgressed individuals collected from Texas, are maintained at the Fort Worth Zoo and on private property in West Texas. Therefore, assessments of standing genetic variation within and among wild and refuge populations and levels of admixture in the wild are critical for future conservation and management planning. Fin clips were acquired in 10 locations in the wild, five in Texas, five in New Mexico and from two refuge populations in Texas (one maintained by Fort Worth Zoo and another on a private property in West Texas). In Texas, non‐introgressed C. pecosensis were found in the wild at only one location Upper Salt Creek (USC); all other locations were composed of admixed individuals or non‐introgressed C. variegatus . No admixed individuals were found in New Mexico. Significant genetic heterogeneity was detected between all locations of non‐introgressed C. pecosensis , including the refuge populations, and estimates of divergence between Texas locations (USC and refuge populations) and New Mexico locations were relatively large ( F ST : 0.23–0.32). Estimates of contemporary effective population size for USC and the two refuge populations were less than 50, but greater than 500 for all New Mexico populations. In summation, while New Mexico populations look secure, the data suggest that C. pecosensis in Texas is currently imperilled by the threat of hybridization, as well as potential loss of genetic diversity on contemporary time scales. Deep divergence between Texas (including refuge populations) and New Mexico suggests that further study would be needed prior to any management plans that would involve assisted gene flow between the regions.

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Conservation genomics of the imperiled Leon springs pupfish, Cyprinodon bovinus, across temporal and spatial scales - Robert J. Bretzing-Tungate; Kevin W. Conway; Megan G. Bean; Ryan K. Smith; Christopher M. Hollenbeck; Andrew T. Fields; Elizabeth P. Dolan; Steven M. Mussmann; David S. Portnoy (Conservation Genetics, 2026)
The Leon Springs pupfish, Cyprinodon bovinus , is federally listed as endangered and currently confined to spring-fed pools on the Diamond Y Spring Preserve in Pecos County, Texas, USA. A refuge population is maintained by U.S. Fish and Wildlife Service in Dexter, New Mexico, USA because of ongoing threats from hybridization with the introduced congener, the sheepshead minnow, C. variegatus. To inform continued conservation and management planning for this species, a comprehensive conservation genomics study using double digest restriction-site associated DNA sequencing was performed. No evidence of contemporary hybridization or recent introgression between C. bovinus and C. variegatus was found. The refuge population was significantly differentiated from wild samples collected at two locations, and the two wild populations (less than 1 km apart) also exhibited significant heterogeneity in allele frequencies. Estimates of within population diversity were smaller for wild locations than the refuge population. Correspondingly, the wild populations’ contemporary effective population size estimates were smaller than the refuge’s effective population size estimates (145–262 versus 679). Temporal analyses, involving genetic data collected from samples obtained in 2013, suggest an increased magnitude of drift acting on the wild populations relative to the reserve population. Based on the results of this study, it appears that steps taken in the early 2000s to eradicate genetically admixed individuals from the wild populations were successful. However, habitat fragmentation and small effective population sizes of the wild populations have led to accelerated drift and decreasing levels of within population genetic diversity. This may jeopardize the long-term persistence of C. bovinus .

Water column structure influences variability of micronekton distribution and biodiversity in the California Current - Adena J. Schonfeld; Ryan P. Gasbarro; Megan A. Cimino; John C. Field; Steven J. Bograd; Elliott L. Hazen; Jarrod A. Santora (Progress in Oceanography, 2025)

Mixed stock analysis of major markets and trade records reveals illegal trade of oceanic whitetip shark fins from the Atlantic ocean - Candace Y. A. Fields; Diego Cardeñosa; Andrea Bernard; Kevin A. Feldheim; Stephan W. Gale; Yannis P. Papastamatiou; Kwok Ho Shea; Mahmood S. Shivji; Huarong Zhang; Demian D. Chapman (Conservation Genetics, 2025)

Which Plant Traits Increase Soil Carbon Sequestration? Empirical Evidence From a Long‐Term Poplar Genetic Diversity Trial - John L. Field; Brandon P. Sloan; Matthew E. Craig; Parker Calloway; Sarah L. Ottinger; Thomas Mead; Rose Z. Abramoff; Mirko Pavicic Venegas; Hari B. Chhetri; Kathy Haiby; Udaya C. Kalluri; Wellington Muchero; et al. (Global Change Biology, 2025)
Plants play a key role in mediating soil response to global change, and breeding or engineering crops to increase soil organic carbon (SOC) storage is a potential route to land‐based carbon dioxide removal in agricultural systems. However, due to limited observational datasets plus shifting paradigms of SOC stabilization, it is unclear which plant traits are most important for enhancing different types of soil organic matter. Existing long‐term common gardens of genetically diverse plant populations may provide an opportunity to evaluate biological controls on SOC, separate from environmental or management variability. Here we report on soil and root chemical data collected for 24 genotypes within a 13‐year‐old common garden in northwestern Oregon planted with a large natural variant population of Populus trichocarpa . Fractionating surface soil (0–15 cm) revealed substantial variation in stocks of mineral‐associated organic matter (MAOM; 18–67 t C/ha) and particulate organic matter (POM; 2–22 t C/ha). Tree genotype explained 24% and 26% of the MAOM and POM stock variability, respectively, after controlling for background variability. We found minimal association between SOC concentration and either aboveground tree productivity or root biomass recalcitrance (C/N ratios and lignin content). In contrast, root elemental content appeared influential for MAOM‐C concentration, which showed a strong positive association with root aluminum (Al) and a strong negative association with root boron (B) and magnesium (Mg). Furthermore, root concentrations of these elements were highly heritable (57%–78%) and not simply a reflection of background variation in soil elemental concentrations. We estimate that surface SOC stocks under these 24 genotypes have diverged at rates of up to 1.2–4.3 t C/ha/year. These results suggest that long‐term genetic diversity trials have value for elucidating biological controls on soil organic matter dynamics, and that traits associated with root elemental content may be a useful target for enhancing biosequestration.

Penetration of groundwater into crystalline rocks - Bruce W. D. Yardley; Roy A. Wogelius; Thomas Mueller; Antoni E. Milodowski; Lorraine P. Field; Lin Ma; Richard Metcalfe; Simon Norris (Hydrogeology Journal, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Correction: The history, science and preliminary results from the reintroduction of the chequered skipper, Carterocephalus palaemon into Rockingham forest, England - N. A. D. Bourn; S. O’Riordan; D. Maes; P. Goffart; T. Shadbolt; L. Hordley; A. W. Sainsbury; C. Bulman; D. Hoare; R. Field; J. Curson; J. P. Wildman; et al. (Journal of Insect Conservation, 2025)

Assessing South Africa’s marine protected area quality and progress towards conservation goals: An application of The MPA Guide framework - Laurel C. Field; Kendyl Wright; Jenna Sullivan-Stack; Jean M. Harris; Stephen P. Kirkman; Peter J. Fielding; Ané Oosthuizen; Siyabonga Dlulisa; Anastasiya Laznya; Emanuel J. Gonçalves; Kirsten Grorud-Colvert (Marine Policy, 2025)

Multi-objective optimization of sustainable aviation fuel production pathways in the U.S. Corn Belt - Ece Ari Akdemir; Jordan Kern; Jack P. Smith; Braden J. Limb; Jason C. Quinn; John L. Field; Taylor Pack (Biomass and Bioenergy, 2025)

Assessments of expected MPA outcomes can inform and improve biodiversity conservation: Case studies using The MPA Guide - Jenna Sullivan-Stack; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Alexandra Barron; Cassandra M. Brooks; Joachim Claudet; Barbara Horta e Costa; Estradivari; Laurel C. Field; Sylvaine Giakoumi; Emanuel Gonçalves; Natalie Groulx; et al. (Marine Policy, 2024)

Biochar-Sulfate Reducing Bacteria synergy: A green approach for antimony removal and recovery from high-concentrated waters - Marina M. Atilano-Camino; Ana P. Canizales Laborín; Angelita M. Ortega Juárez; M. Rosario Sánchez-Macías; Iván Moreno-Andrade; Reyes Sierra-Álvarez; Jim Field; Christopher Rensing; Julián Carrillo-Reyes; Francisco J. Cervantes; Aurora M. Pat-Espadas (Journal of Environmental Chemical Engineering, 2024)

The history, science and preliminary results from the reintroduction of the Chequered Skipper, Carterocephalus palaemon into Rockingham Forest, England - N. A. D. Bourn; S. O’Riordan; D. Maes; P. Goffart; T. Shadbolt; L. Hordley; A. W. Sainsbury; C. Bulman; D. Hoare; R. Field; J. Curson; J. P. Wildman; et al. (Journal of Insect Conservation, 2024)
Habitat loss and fragmentation have caused declines in the abundance and distribution of butterflies, particularly habitat specialists. The Chequered Skipper, Carterocephalus palaemon , has been extinct in England since 1976 after declining from the 1940s predominantly due to changes in woodland management including afforestation and the decline in traditional coppice management. To enable C. palaemon to flourish again, this species was reintroduced from Belgium to England in 2018 with the aim of establishing a resident breeding population. Here, we report on the recent reintroduction, outlining the reintroduction method used, the establishment status of the species in England, the clinical health of reintroduced individuals, and post-release monitoring results. Furthermore, we assess the habitat suitability of sites around the original release site to determine which were similar to the current re-location site and could be used for future reintroductions, and to aid the targeting of further management to increase habitat suitability. Since 2018, 128 Chequered Skipper butterflies have been reintroduced from Belgium to Rockingham Forest in England. Health examinations demonstrated that individuals were healthy, and this in part resulted in the population establishing at the first release site and the area of occupancy increasing each year to 2022. However, the reintroduced population has yet to naturally colonise other areas within Rockingham Forest and therefore is not yet a functioning metapopulation. Despite the project still being in its infancy, we are able to report on a successful five years. Implications for insect conservation: Rigorous scientific research has provided the evidence to support reintroductions, and will continue to be used to ensure the ecology and population dynamics of this species is sufficiently understood so that Chequered Skipper populations can thrive again in England.

Selection and characterization of a Parachlorella kessleri microalgal strain able to assimilate lactose, and grow on dairy waste - Nora Hidasi; Amr Badary; Hunter D. Jenkins; Francis J. Fields; Stephen P. Mayfield; Simone Ferrari (Biomass and Bioenergy, 2024)

Ecology of fear alters behavior of grizzly bears exposed to bear‐viewing ecotourism - Monica L. Short; Christina N. Service; Justin P. Suraci; Kyle A. Artelle; Kate A. Field; Chris T. Darimont (Ecology, 2024)
Humans are perceived as predators by many species and may generate landscapes of fear, influencing spatiotemporal activity of wildlife. Additionally, wildlife might seek out human activity when faced with predation risks (human shield hypothesis). We used the anthropause, a decrease in human activity resulting from the COVID‐19 pandemic, to test ecology of fear and human shield hypotheses and quantify the effects of bear‐viewing ecotourism on grizzly bear ( Ursus arctos ) activity. We deployed camera traps in the Khutze watershed in Kitasoo Xai'xais Territory in the absence of humans in 2020 and with experimental treatments of variable human activity when ecotourism resumed in 2021. Daily bear detection rates decreased with more people present and increased with days since people were present. Human activity was also associated with more bear detections at forested sheltered sites and less at exposed sites, likely due to the influence of habitat on bear perception of safety. The number of people negatively influenced adult male detection rates, but we found no influence on female with young detections, providing no evidence that females responded behaviorally to a human shield effect from reduced male activity. We also observed apparent trade‐offs of risk avoidance and foraging. When salmon levels were moderate to high, detected bears were more likely to be females with young than adult males on days with more people present. Should managers want to minimize human impacts on bear activity and maintain baseline age–sex class composition at ecotourism sites, multiday closures and daily occupancy limits may be effective. More broadly, this work revealed that antipredator responses can vary with intensity of risk cues, habitat structure, and forage trade‐offs and manifest as altered age–sex class composition of individuals using human‐influenced areas, highlighting that wildlife avoid people across multiple spatiotemporal scales.

Stereo-video landers can rapidly assess marine fish diversity and community assemblages - Kinsey E. Matthews; Ryan T. Fields; Kathleen P. Cieri; Jacklyn L. Mohay; Mary G. Gleason; Richard M. Starr (Frontiers in Marine Science, 2024)
Climate change and anthropogenic stressors affect the distribution, abundance, and diversity of fish communities across the world. To understand rapidly changing biotic communities, resource managers need a method to quickly and efficiently document temporal and spatial changes in community assemblages across various spatial scales. In this study, we describe the use of new video lander tools to survey fish communities in rocky marine habitats on the continental shelf and slope in California, USA. We evaluate how fish diversity metrics determined by video surveys vary among geographically distinct areas. Our results demonstrate that species diversity, evenness, and richness vary spatially across the coast. Furthermore, community assemblages differ at both broad and fine spatial scales because of differences among habitats. Length frequencies and densities of species in this study were similar to those reported in previous studies. As community assemblages and biodiversity metrics shift in response to changing stressors, it is increasingly important to develop tools and methodologies to detect and rapidly monitor these changes.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Development, verification, and implementation of an eDNA detection assay for emydids with a case study on diamondback terrapins, Malaclemys terrapin, and red eared slider, Trachemys script elegans - Andrew T. Fields; Elizabeth P. Hunt; Katherine Lanoue; Aaron S. Baxter; Riley S. Sebby; W. Jay Tarkington; David S. Portnoy (Conservation Genetics Resources, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Evaluating the sustainability of the 2017 US biofuel industry with an integrated techno-economic analysis and life cycle assessment - Jack P. Smith; Braden J. Limb; Colin M. Beal; Kelly R. Banta; John L. Field; Steven J. Simske; Jason C. Quinn (Journal of Cleaner Production, 2023)

Automated detection, delineation and quantification of whole-body bone metastasis using FDG-PET/CT images - R. Nigam; M. Field; G. Harris; M. Barton; M. Carolan; P. Metcalfe; L. Holloway (Physical and Engineering Sciences in Medicine, 2023)
Non-small cell lung cancer (NSCLC) patients with the metastatic spread of disease to the bone have high morbidity and mortality. Stereotactic ablative body radiotherapy increases the progression free survival and overall survival of these patients with oligometastases. FDG-PET/CT, a functional imaging technique combining positron emission tomography (PET) with 18 F-fluorodeoxyglucose (FDG) and computer tomography (CT) provides improved staging and identification of treatment response. It is also associated with reduction in size of the radiotherapy tumour volume delineation compared with CT based contouring in radiotherapy, thus allowing for dose escalation to the target volume with lower doses to the surrounding organs at risk. FDG-PET/CT is increasingly being used for the clinical management of NSCLC patients undergoing radiotherapy and has shown high sensitivity and specificity for the detection of bone metastases in these patients. Here, we present a software tool for detection, delineation and quantification of bone metastases using FDG-PET/CT images. The tool extracts standardised uptake values (SUV) from FDG-PET images for auto-segmentation of bone lesions and calculates volume of each lesion and associated mean and maximum SUV. The tool also allows automatic statistical validation of the auto-segmented bone lesions against the manual contours of a radiation oncologist. A retrospective review of FDG-PET/CT scans of more than 30 candidate NSCLC patients was performed and nine patients with one or more metastatic bone lesions were selected for the present study. The SUV threshold prediction model was designed by splitting the cohort of patients into a subset of ‘development’ and ‘validation’ cohorts. The development cohort yielded an optimum SUV threshold of 3.0 for automatic detection of bone metastases using FDG-PET/CT images. The validity of the derived optimum SUV threshold on the validation cohort demonstrated that auto-segmented and manually contoured bone lesions showed strong concordance for volume of bone lesion ( r = 0.993) and number of detected lesions ( r = 0.996). The tool has various applications in radiotherapy, including but not limited to studies determining optimum SUV threshold for accurate and standardised delineation of bone lesions and in scientific studies utilising large patient populations for instance for investigation of the number of metastatic lesions that can be treated safety with an ablative dose of radiotherapy without exceeding the normal tissue toxicity.

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Large‐scale, multidecade monitoring data from kelp forest ecosystems in California and Oregon ( USA ) - Daniel P. Malone; Kathryn Davis; Steve I. Lonhart; Avrey Parsons‐Field; Jennifer E. Caselle; Mark H. Carr (Ecology, 2022)
Kelp forests are among the most productive ecosystems on Earth. In combination with their close proximity to the shore, the productivity and biodiversity of these ecosystems generate a wide range of ecosystem services including supporting (e.g., primary production, habitat), regulating (e.g., water flow, coastal erosion), provisioning (e.g., commercial and recreational fisheries), and cultural (e.g., recreational, artisanal) services. For these reasons, kelp forests have long been the target of ecological studies. However, with few exceptions, these studies have been localized and short term ( a concentration, sea surface temperature, wave energy) in explaining observed spatial and temporal patterns. For this purpose, the ecological community (i.e., density, percent cover, or biomass of conspicuous fishes, invertebrates, and macroalgae) and geomorphological attributes (bottom depth, substratum type, and vertical relief) of kelp forest ecosystems have been surveyed annually using SCUBA divers trained in both scientific diving and data collection techniques and the identification of kelp forest species. The study region spans distinct ecological and biogeographic provinces, which enables investigations of how variation in environmental drivers and distinctive species compositions influence community structure, and its response to climate‐related environmental change across a portion of the California Current Large Marine Ecosystem. These data have been used to inform fisheries management, design and evaluate California's state‐wide network of marine protected areas (MPAs), and assess the ecological consequences of climate change (e.g., marine heatwaves). Over time, the spatial and temporal design of the monitoring program was adapted to fill its role in evaluating the ecological responses to the establishment of MPAs. There are no copyright restrictions; please cite this paper when data are used.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Peripartum cardiomyopathy: a global effort to find the cause and cure for the rare and little understood disease - Amy Li; K. Campbell; S. Lal; Y. Ge; A. Keogh; P. S. Macdonald; P. Lau; John Lai; W. A. Linke; J. Van der Velden; A. Field; B. Martinac; et al. (Biophysical Reviews, 2022)
In this review, we present our current understanding of peripartum cardiomyopathy (PPCM) based on reports of the incidence, diagnosis and current treatment options. We summarise opinions on whether PPCM is triggered by vascular and/or hormonal causes and examine the influence of comorbidities such as preeclampsia. Two articles published in 2021 strongly support the hypothesis that PPCM may be a familial disease. Using large cohorts of PPCM patients, they summarised the available genomic DNA sequence data that are expressed in human cardiomyocytes. While PPCM is considered a disease predominately affecting the left ventricle, there are data to suggest that some cases also involve right ventricular failure. Finally, we conclude that there is sufficient evidence to warrant an RNAseq investigation and that this would be most informative if performed at the cardiomyocytes level rather than analysing genomic DNA from the peripheral circulation. Given the rarity of PPCM, the combined resources of international human heart tissue biobanks have assembled 30 ventricular tissue samples from PPCM patients, and we are actively seeking to enlarge this patient base by collaborating with human heart tissue banks and research laboratories who would like to join this endeavour.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

The relationship between niche breadth and range size of beech ( Fagus ) species worldwide - Qiong Cai; Erik Welk; Chengjun Ji; Wenjing Fang; Francesco M. Sabatini; Jianxiao Zhu; Jiangling Zhu; Zhiyao Tang; Fabio Attorre; Juan A. Campos; Andraž Čarni; Milan Chytrý; et al. (Journal of Biogeography, 2021)
Aim This work explores whether the commonly observed positive range size–niche breadth relationship exists for Fagus , one of the most dominant and widespread broad‐leaved deciduous tree genera in temperate forests of the Northern Hemisphere. Additionally, we ask whether the 10 extant Fagus species’ niche breadths and climatic tolerances are under phylogenetic control. Location Northern Hemisphere temperate forests. Taxon Fagus L. Methods Combining the global vegetation database sPlot with Chinese vegetation data, we extracted 107,758 relevés containing Fagus species. We estimated biotic and climatic niche breadths per species using plot‐based co‐occurrence data and a resource‐based approach, respectively. We examined the relationships of these estimates with range size and tested for their phylogenetic signal, prior to which a Random Forest (RF) analysis was applied to test which climatic properties are most conserved across the Fagus species. Results Neither biotic niche breadth nor climatic niche breadth was correlated with range size, and the two niche breadths were incongruent as well. Notably, the widespread North American F. grandifolia had a distinctly smaller biotic niche breadth than the Chinese Fagus species ( F. engleriana , F. hayatae , F. longipetiolata and F. lucida ) with restricted distributions in isolated mountains. The RF analysis revealed that cold tolerance did not differ among the 10 species, and thus may represent an ancestral, fixed trait. In addition, neither biotic nor climatic niche breadths are under phylogenetic control. Main Conclusions We interpret the lack of a general positive range size–niche breadth relationship within the genus Fagus as a result of the widespread distribution, high among‐region variation in available niche space, landscape heterogeneity and Quaternary history. The results hold when estimating niche sizes either by fine‐scale co‐occurrence data or coarse‐scale climate data, suggesting a mechanistic link between factors operating across spatial scales. Besides, there was no evidence for diverging ecological specialization within the genus Fagus .

Identifying human health risks from precious metal mining in Sierra Leone - Richard A. Marcantonio; Sean P. Field; Papanie Bai Sesay; Gary A. Lamberti (Regional Environmental Change, 2021)

High uncertainty over the future of tidal marsh birds under current sea-level rise projections - Brian T. Klingbeil; Jonathan B. Cohen; Maureen D. Correll; Christopher R. Field; Thomas P. Hodgman; Adrienne I. Kovach; Erika E. Lentz; Brian J. Olsen; W. Gregory Shriver; Whitney A. Wiest; Chris S. Elphick (Biodiversity and Conservation, 2021)

Extinction risk and conservation gaps for Aloe (Asphodelaceae) in the Horn of Africa - Steven P. Bachman; Paul Wilkin; Tom Reader; Richard Field; Odile Weber; Inger Nordal; Sebsebe Demissew (Biodiversity and Conservation, 2020)
Identification of conservation priorities is essential for conservation planning, especially as the biodiversity crisis develops. We aimed to support conservation prioritisation by addressing knowledge gaps for the genus Aloe in the Horn of Africa. Specifically, we developed a dataset of herbarium voucher specimens and occurrence data to estimate geographic distribution of 88 species of Aloe and used this to estimate extinction risk and establish the major threats to Aloe in this region. The resulting assessments, each published on the IUCN Red List, show that 39% of the species are threatened with extinction, and the principal threats are the expansion and intensification of crop farming and livestock farming, gathering of plants, and unintentional effects of logging and wood harvesting. We review ex situ conservation in botanic gardens and seed banks, revealing gaps in coverage and urgent priorities for collection, with 25 threatened Aloe species currently unrepresented in seed banks. Protected areas in the region offer limited coverage of Aloe distributions and the most recently designated protected areas are increasingly in regions that do not overlap with Aloe distributions. However, we show with a simple optimisation approach that even a modest increase in protected area of 824 square kilometres would allow representation of all Aloe species, although further data are needed to test the area required to ensure long-term persistence (resilience) of Aloe species.

Framework for quantifying population responses to disturbance reveals that coastal birds are highly resilient to hurricanes - Christopher R. Field; Katharine J. Ruskin; Jonathan B. Cohen; Thomas P. Hodgman; Adrienne I. Kovach; Brian J. Olsen; W. Gregory Shriver; Chris S. Elphick (Ecology Letters, 2019)
Changes in the frequency and severity of extreme weather may introduce new threats to species that are already under stress from gradual habitat loss and climate change. We provide a probabilistic framework that quantifies potential threats by applying concepts from ecological resilience to single populations. Our approach uses computation to compare disturbance–impacted projections to a population's normal range of variation, quantifying the full range of potential impacts. We illustrate this framework with projection models for coastal birds, which are commonly depicted as vulnerable to disturbances, especially hurricanes and oil spills. We found that populations of coastal specialists are resilient to extreme disturbances, with high resistance to the effects of short‐term reductions in vital rates and recovery within 20 years. Applying the general framework presented here across disturbance‐prone species and ecosystems would improve understanding of population resilience and generate specific projections of resilience that are needed for effective conservation planning.

Parasite‐mediated selection in a natural metapopulation of Daphnia magna - Andrea P. Cabalzar; Peter D. Fields; Yasuhiko Kato; Hajime Watanabe; Dieter Ebert (Molecular Ecology, 2019)
Parasite‐mediated selection varying across time and space in metapopulations is expected to result in host local adaptation and the maintenance of genetic diversity in disease‐related traits. However, nonadaptive processes like migration and extinction‐(re)colonization dynamics might interfere with adaptive evolution. Understanding how adaptive and nonadaptive processes interact to shape genetic variability in life‐history and disease‐related traits can provide important insights into their evolution in subdivided populations. Here we investigate signatures of spatially fluctuating, parasite‐mediated selection in a natural metapopulation of Daphnia magna . Host genotypes from infected and uninfected populations were genotyped at microsatellite markers, and phenotyped for life‐history and disease traits in common garden experiments. Combining phenotypic and genotypic data a Q ST – F ST ‐like analysis was conducted to test for signatures of parasite mediated selection. We observed high variation within and among populations for phenotypic traits, but neither an indication of host local adaptation nor a cost of resistance. Infected populations have a higher gene diversity ( H s) than uninfected populations and H s is strongly positively correlated with fitness. These results suggest a strong parasite effect on reducing population level inbreeding. We discuss how stochastic processes related to frequent extinction‐(re)colonization dynamics as well as host and parasite migration impede the evolution of resistance in the infected populations. We suggest that the genetic and phenotypic patterns of variation are a product of dynamic changes in the host gene pool caused by the interaction of colonization bottlenecks, inbreeding, immigration, hybrid vigor, rare host genotype advantage and parasitism. Our study highlights the effect of the parasite in ameliorating the negative fitness consequences caused by the high drift load in this metapopulation.

Many unreported crop pests and pathogens are probably already present - Daniel P. Bebber; Elsa Field; Heng Gui; Peter Mortimer; Timothy Holmes; Sarah J. Gurr (Global Change Biology, 2019)
Invasive species threaten global biodiversity, food security and ecosystem function. Such incursions present challenges to agriculture where invasive species cause significant crop damage and require major economic investment to control production losses. Pest risk analysis (PRA) is key to prioritize agricultural biosecurity efforts, but is hampered by incomplete knowledge of current crop pest and pathogen distributions. Here, we develop predictive models of current pest distributions and test these models using new observations at subnational resolution. We apply generalized linear models (GLM) to estimate presence probabilities for 1,739 crop pests in the CABI pest distribution database. We test model predictions for 100 unobserved pest occurrences in the People's Republic of China (PRC), against observations of these pests abstracted from the Chinese literature. This resource has hitherto been omitted from databases on global pest distributions. Finally, we predict occurrences of all unobserved pests globally. Presence probability increases with host presence, presence in neighbouring regions, per capita GDP and global prevalence. Presence probability decreases with mean distance from coast and known host number per pest. The models are good predictors of pest presence in provinces of the PRC, with area under the ROC curve (AUC) values of 0.75–0.76. Large numbers of currently unobserved, but probably present pests (defined here as unreported pests with a predicted presence probability >0.75), are predicted in China, India, southern Brazil and some countries of the former USSR. We show that GLMs can predict presences of pseudoabsent pests at subnational resolution. The Chinese literature has been largely inaccessible to Western academia but contains important information that can support PRA. Prior studies have often assumed that unreported pests in a global distribution database represent a true absence. Our analysis provides a method for quantifying pseudoabsences to enable improved PRA and species distribution modelling.

Bulk phase resource ratio alters carbon steel corrosion rates and endogenously produced extracellular electron transfer mediators in a sulfate-reducing biofilm - Gregory P. Krantz; Kilean Lucas; Erica L.- Wunderlich; Linh T. Hoang; Recep Avci; Gary Siuzdak; Matthew W. Fields (Biofouling, 2019)

Crown-of-thorns starfish impede the recovery potential of coral reefs following bleaching - M. D. E. Haywood; D. P. Thomson; R. C. Babcock; R. D. Pillans; J. K. Keesing; M. Miller; W. A. Rochester; A. Donovan; R. D. Evans; G. Shedrawi; S. N. Field (Marine Biology, 2019)

Refining area of occupancy to address the modifiable areal unit problem in ecology and conservation - Justin Moat; Steven P. Bachman; Richard Field; Doreen S. Boyd (Conservation Biology, 2018)
The modifiable areal unit problem is prevalent across many aspects of spatial analysis within ecology and conservation. The problem is particularly manifested when calculating metrics for extinction risk estimation, for example, area of occupancy (AOO). Although embedded in the International Union for the Conservation of Nature (IUCN) Red List criteria, AOO is often not used or is poorly applied. We evaluated new and existing methods for calculating AOO from occurrence records and devised a method for determining the minimum AOO with a uniform grid. We evaluated the grid cell shape, origin, and rotation with real‐world and simulated data and reviewed the effects on AOO values and possible impacts for species already assessed on the IUCN Red List. The AOO varied by up to 80%, and a ratio of cells to points of 1:1.21 yielded the maximum variation in the number of occupied cells. These findings potentially impact 3% of existing species on the IUCN Red List and species not yet assessed. Our new method combined grid rotation and moving grid origin and gave fast, robust, and reproducible results and, in the majority of cases, achieved the minimum AOO. As well as determining minimum AOO, our method yielded a confidence interval that should be incorporated into existing tools that support species risk assessment. We recommend when recording AOO and other areal measurements that the methods; summary statistics across multiple iterations; angle and origin of the minimum grid; map projection; and datum be recorded, this will lead to more robust species risk assessments.

Environmental barriers to sociality in an obligate eusocial sweat bee - P. J. Davison; J. Field (Insectes Sociaux, 2018)

Spiroplasma dominates the microbiome of khapra beetle: comparison with a congener, effects of life stage and temperature - D. M. Wilches; R. A. Laird; P. G. Fields; P. Coghlin; K. D. Floate (Symbiosis, 2018)

The global overlap of bioenergy and carbon sequestration potential - P. A. Turner; K. J. Mach; D. B. Lobell; S. M. Benson; E. Baik; D. L. Sanchez; C. B. Field (Climatic Change, 2018)

Decoupled dimensions of leaf economic and anti-herbivore defense strategies in a tropical canopy tree community - K. McManus Chauvin; G. P. Asner; R. E. Martin; W. J. Kress; S. J. Wright; C. B. Field (Oecologia, 2018)

Limited social plasticity in the socially polymorphic sweat bee Lasioglossum calceatum - P. J. Davison; J. Field (Behavioral Ecology and Sociobiology, 2018)

Spatial population genetic structure of a bacterial parasite in close coevolution with its host - Jason P. Andras; Peter D. Fields; Dieter Ebert (Molecular Ecology, 2018)
Knowledge of a species’ population genetic structure can provide insight into fundamental ecological and evolutionary processes including gene flow, genetic drift and adaptive evolution. Such inference is of particular importance for parasites, as an understanding of their population structure can illuminate epidemiological and coevolutionary dynamics. Here, we describe the population genetic structure of the bacterium Pasteuria ramosa , a parasite that infects planktonic crustaceans of the genus Daphnia . This system has become a model for investigations of host–parasite interactions and represents an example of coevolution via negative frequency‐dependent selection (aka “Red Queen” dynamics). To sample P. ramosa , we experimentally infected a panel of Daphnia hosts with natural spore banks from the sediments of 25 ponds throughout much of the species range in Europe and western Asia. Using 12 polymorphic variable number tandem repeat loci ( VNTR loci), we identified substantial genetic diversity, both within and among localities, that was structured geographically among ponds. Genetic diversity was also structured among host genotypes within ponds, although this pattern varied by locality, with P. ramosa at some localities partitioned into distinct host‐specific lineages, and other localities where recombination had shuffled genetic variation among different infection phenotypes. Across the sample range, there was a pattern of isolation by distance, and principal components analysis coupled with Procrustes rotation identified congruence between patterns of genetic variation and geography. Our findings support the hypothesis that Pasteuria is an endemic parasite coevolving closely with its host. These results provide important context for previous studies of this model system and inform hypotheses for future research.

Human Immunodeficiency Virus Promotes Mitochondrial Toxicity - Summer J. Rozzi; Valeria Avdoshina; Jerel A. Fields; Margarita Trejo; Hoai T. Ton; Gerard P. Ahern; Italo Mocchetti (Neurotoxicity Research, 2017)

Modelling native and alien vascular plant species richness: At which scales is geodiversity most relevant? - Joseph J. Bailey; Doreen S. Boyd; Jan Hjort; Chris P. Lavers; Richard Field (Global Ecology and Biogeography, 2017)
Aim To explore the scale dependence of relationships between novel measures of geodiversity and species richness of both native and alien vascular plants. Location Great Britain. Time period Data collected 1995–2015. Major taxa Vascular plants. Methods We calculated the species richness of terrestrial native and alien vascular plants (6,932 species in total) across the island of Great Britain at grain sizes of 1 km 2 ( n = 219,964) and 100 km 2 ( n = 2,121) and regional extents of 25–250 km diameter, centred around each 100‐km 2 cell. We compiled geodiversity data on landforms, soils, hydrological and geological features using existing national datasets, and used a newly developed geomorphometric method to extract landform coverage data (e.g., hollows, ridges, valleys, peaks). We used these as predictors of species richness alongside climate, commonly used topographic metrics, land‐cover variety and human population. We analysed species richness across scales using boosted regression tree (BRT) modelling and compared models with and without geodiversity data. Results Geodiversity significantly improved models over and above the widely used topographic metrics, particularly at smaller extents and the finer grain size, and slightly more so for native species richness. For each increase in extent, the contribution of climatic variables increased and that of geodiversity decreased. Of the geodiversity variables, automatically extracted landform data added the most explanatory power, but hydrology (rivers, lakes) and materials (soil, superficial deposits, geology) were also important. Main conclusions Geodiversity improves our understanding of, and our ability to model, the relationship between species richness and abiotic heterogeneity at multiple spatial scales by allowing us to get closer to the real‐world physical processes that affect patterns of life. The greatest benefit comes from measuring the constituent parts of geodiversity separately rather than one combined variable (as in most of the few studies to date). Automatically extracted landform data, the use of which is novel in ecology and biogeography, proved particularly valuable in our study.

Training in the Conduct of Population-Based Multi-Site and Multi-Disciplinary Studies: the Cancer Research Network’s Scholars Program - Diana S. M. Buist; Terry S. Field; Matthew P. Banegas; Heather A. Clancy; V. Paul Doria-Rose; Mara M. Epstein; Robert T. Greenlee; Sarah McDonald; Hazel B. Nichols; Pamala A. Pawloski; Lawrence H. Kushi (Journal of Cancer Education, 2017)

Transgenic citrus plants expressing the p35 anti-apoptotic gene have altered response to abiotic stress - Vladimir Orbović; Jeb S. Fields; James P. Syvertsen (Horticulture, Environment, and Biotechnology, 2017)

Experimental fire increases soil carbon dioxide efflux in a grassland long‐term multifactor global change experiment - Aaron L. Strong; Tera P. Johnson; Nona R. Chiariello; Christopher B. Field (Global Change Biology, 2017)
Numerous studies have demonstrated that soil respiration rates increase under experimental warming, although the long‐term, multiyear dynamics of this feedback are not well constrained. Less is known about the effects of single, punctuated events in combination with other longer‐duration anthropogenic influences on the dynamics of soil carbon (C) loss. In 2012 and 2013, we assessed the effects of decadal‐scale anthropogenic global change – warming, increased nitrogen (N) deposition, elevated carbon dioxide ( CO 2 ), and increased precipitation – on soil respiration rates in an annual‐dominated Mediterranean grassland. We also investigated how controlled fire and an artificial wet‐up event, in combination with exposure to the longer‐duration anthropogenic global change factors, influenced the dynamics of C cycling in this system. Decade‐duration surface soil warming (1–2 °C) had no effect on soil respiration rates, while +N addition and elevated CO 2 concentrations increased growing‐season soil CO 2 efflux rates by increasing annual aboveground net primary production ( NPP ) and belowground fine root production, respectively. Low‐intensity experimental fire significantly elevated soil CO 2 efflux rates in the next growing season. Based on mixed‐effects modeling and structural equation modeling, low‐intensity fire increased growing‐season soil respiration rates through a combination of three mechanisms: large increases in soil temperature (3–5 °C), significant increases in fine root production, and elevated aboveground NPP . Our study shows that in ecosystems where soil respiration has acclimated to moderate warming, further increases in soil temperature can stimulate greater soil CO 2 efflux. We also demonstrate that punctuated short‐duration events such as fire can influence soil C dynamics with implications for both the parameterization of earth system models ( ESM s) and the implementation of climate change mitigation policies that involve land‐sector C accounting.

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

Regulation of host colony activity by the social parasite Polistes semenowi - J. P. Green; E. J. Almond; J. Williamson; J. Field (Insectes Sociaux, 2016)

Social polymorphism in the sweat bee Lasioglossum (Evylaeus) calceatum - P. J. Davison; J. Field (Insectes Sociaux, 2016)

Interdependence of DNA mismatch repair proteins MLH1 and MSH2 in apoptosis in human colorectal carcinoma cell lines - Samar Hassen; Akhtar A. Ali; Surya P. Kilaparty; Qudes A. Al-Anbaky; Waqar Majeed; Bruce M. Boman; Jeremy Z. Fields; Nawab Ali (Molecular and Cellular Biochemistry, 2016)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Nasal chondromesenchymal hamartomas arise secondary to germline and somatic mutations of DICER1 in the pleuropulmonary blastoma tumor predisposition disorder - Douglas R. Stewart; Yoav Messinger; Gretchen M. Williams; Jiandong Yang; Amanda Field; Kris Ann P. Schultz; Laura A. Harney; Leslie A. Doros; Louis P. Dehner; D. Ashley Hill (Human Genetics, 2014)

Identification and Expression Profile of Two Putative Odorant-Binding Proteins from the Neotropical Brown Stink Bug, Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) - L R Farias; D P Paula; J J Zhou; R Liu; G J Pappas; M C B Moraes; R A Laumann; M Borges; M A Birkett; J A Pickett; L M Field; S N Báo (Neotropical Entomology, 2014)

Review of treatment methods to remove Wolbachia bacteria from arthropods - Y.-Y. Li; K. D. Floate; P. G. Fields; B.-P. Pang (Symbiosis, 2014)

Perchlorate contamination of groundwater from fireworks manufacturing area in South India - Tomohiko Isobe; Shohei P. Ogawa; Rina Sugimoto; Karri Ramu; Agus Sudaryanto; Govindan Malarvannan; Gnanasekaran Devanathan; Babu Rajendran Ramaswamy; Natesan Munuswamy; Deavaraj Sankar Ganesh; Jeyaraj Sivakumar; A. Sethuraman; et al. (Environmental Monitoring and Assessment, 2013)

A Strategy for Prioritizing Threats and Recovery Actions for At-Risk Species - Catherine R. Darst; Philip J. Murphy; Nathan W. Strout; Steven P. Campbell; Kimberleigh J. Field; Linda Allison; Roy C. Averill-Murray (Environmental Management, 2013)

Use of sodium bicarbonate to stimulate triacylglycerol accumulation in the chlorophyte Scenedesmus sp. and the diatom Phaeodactylum tricornutum - Robert D. Gardner; Keith E. Cooksey; Florence Mus; Richard Macur; Karen Moll; Everett Eustance; Ross P. Carlson; Robin Gerlach; Matthew W. Fields; Brent M. Peyton (Journal of Applied Phycology, 2012)

Refining instrument attachment on phocid seals - Iain C. Field; Robert G. Harcourt; Lars Boehme; P. J. Nico de Bruyn; Jean‐Benoit Charrassin; Clive R. McMahon; Marthán N. Bester; Mike A. Fedak; Mark A. Hindell (Marine Mammal Science, 2012)

Neutral metallated and meso-substituted porphyrins as antimicrobial agents against Gram-positive pathogens - W. N. Burda; K. B. Fields; J. B. Gill; R. Burt; M. Shepherd; X. P. Zhang; L. N. Shaw (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Social and genetic structure in colonies of the social wasp Microstigmus nigrophthalmus - E. R. Lucas; R. P. Martins; L. R. S. Zanette; J. Field (Insectes Sociaux, 2011)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Survival and persistence of human and ruminant‐specific faecal Bacteroidales in freshwater microcosms - Sarah P. Walters; Katharine G. Field (Environmental Microbiology, 2009)
Summary Amplification of host‐specific markers from Bacteroidales faecal anaerobes can rapidly identify the source of faecal pollution. It is necessary to understand persistence and survival of these markers and marker cells, both to interpret quantitative source‐tracking data, and to use such data to predict pathogen occurrence. We measured marker persistence and cell survival of two human (HF134, HF183) and two ruminant (CF128, CF193) faecal Bacteroidales markers, compared with Escherichia coli and enterococci. Freshwater microcosms were inoculated with fresh cattle or human faeces and incubated at 13°C in natural light or darkness. Marker persistence was measured by polymerase chain reaction (PCR) and quantitative PCR. Survival of marker cells was measured by real‐time quantitative PCR. There was no difference in persistence between the two human‐specific Bacteroidales DNA markers in the light and dark microcosms. Cell survival profiles of the two human markers were also similar; both were significantly affected by light. Ruminant markers persisted and survived longer than human markers (14 versus 6 days respectively). CF193 decreased more rapidly than CF128, and light significantly affected CF128 but not CF193. These results support use of host‐specific faecal Bacteroidales markers as indicators of recent faecal pollution, but suggest that caution is needed in interpreting quantitative results to indicate proportional contribution of different sources, as individual markers differ in their survival, persistence and response to environmental variables. The survival and persistence profiles for Bacteroidales markers are consistent with survival profiles for several faecal pathogens.

Occurrence and characterization of Salmonella enterica subspecies enterica serovar 9,12:l,v:- strains from Bulgaria, Denmark, and the United States - P. Petrov; R. S. Hendriksen; T. Kantardjiev; G. Asseva; G. Sørensen; P. Fields; M. Mikoleit; J. Whichard; J. R. McQuiston; M. Torpdahl; F. M. Aarestrup; F. J. Angulo (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

An EST database for Liriodendron tulipifera L. floral buds: the first EST resource for functional and comparative genomics in Liriodendron - Haiying Liang; John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Lukas A. Mueller; Matyas Buzgo; Lena L. Landherr; Yi Hu; D. Scott DiLoreto; Daniel C. Ilut; Dawn Field; Steven D. Tanksley; et al. (Tree Genetics & Genomes, 2008)

Presence–Absence versus Abundance Data for Monitoring Threatened Species - LIANA N. JOSEPH; SCOTT A. FIELD; CHRIS WILCOX; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Effective detection of population trend is crucial for managing threatened species. Little theory exists, however, to assist managers in choosing the most cost‐effective monitoring techniques for diagnosing trend. We present a framework for determining the optimal monitoring strategy by simulating a manager collecting data on a declining species, the Chestnut‐rumped Hylacola ( Hylacola pyrrhopygia parkeri ), to determine whether the species should be listed under the IUCN (World Conservation Union) Red List. We compared the efficiencies of two strategies for detecting trend, abundance, and presence–absence surveys, under financial constraints. One might expect the abundance surveys to be superior under all circumstances because more information is collected at each site. Nevertheless, the presence–absence data can be collected at more sites because the surveyor is not obliged to spend a fixed amount of time at each site. The optimal strategy for monitoring was very dependent on the budget available. Under some circumstances, presence–absence surveys outperformed abundance surveys for diagnosing the IUCN Red List categories cost‐effectively. Abundance surveys were best if the species was expected to be recorded more than 16 times/year; otherwise, presence–absence surveys were best. The relationship between the strategies we investigated is likely to be relevant for many comparisons of presence–absence or abundance data. Managers of any cryptic or low‐density species who hope to maximize their success of estimating trend should find an application for our results.

Interpreting tracer breakthrough tailing in a conduit-dominated karstic aquifer - N. Massei; H. Q. Wang; M. S. Field; J. P. Dupont; J. Rodet (Hydrogeology Journal, 2006)

Interpreting tracer breakthrough tailing in a conduit-dominated karstic aquifer - N. Massei; H. Q. Wang; M. S. Field; J. P. Dupont; M. Bakalowicz; J. Rodet (Hydrogeology Journal, 2006)

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

Adaptive Evolution of Multicolored Fluorescent Proteins in Reef-Building Corals - Steven F. Field; Maria Y. Bulina; Ilya V. Kelmanson; Joseph P. Bielawski; Mikhail V. Matz (Journal of Molecular Evolution, 2006)

Zero tolerance ecology: improving ecological inference by modelling the source of zero observations - Tara G. Martin; Brendan A. Wintle; Jonathan R. Rhodes; Petra M. Kuhnert; Scott A. Field; Samantha J. Low‐Choy; Andrew J. Tyre; Hugh P. Possingham (Ecology Letters, 2005)
A common feature of ecological data sets is their tendency to contain many zero values. Statistical inference based on such data are likely to be inefficient or wrong unless careful thought is given to how these zeros arose and how best to model them. In this paper, we propose a framework for understanding how zero‐inflated data sets originate and deciding how best to model them. We define and classify the different kinds of zeros that occur in ecological data and describe how they arise: either from ‘true zero’ or ‘false zero’ observations. After reviewing recent developments in modelling zero‐inflated data sets, we use practical examples to demonstrate how failing to account for the source of zero inflation can reduce our ability to detect relationships in ecological data and at worst lead to incorrect inference. The adoption of methods that explicitly model the sources of zero observations will sharpen insights and improve the robustness of ecological analyses.

Attentional and approach biases for smoking cues in smokers: an investigation of competing theoretical views of addiction - Karin Mogg; Matt Field; Brendan P. Bradley (Psychopharmacology, 2005)

Alcohol increases cognitive biases for smoking cues in smokers - Matt Field; Karin Mogg; Brendan P. Bradley (Psychopharmacology, 2005)

A model for wave control on coral breakage and species distribution in the Hawaiian Islands - C. D. Storlazzi; E. K. Brown; M. E. Field; K. Rodgers; P. L. Jokiel (Coral Reefs, 2005)

Attentional biases for alcohol cues in heavy and light social drinkers: the roles of initial orienting and maintained attention - Matt Field; Karin Mogg; Jessica Zetteler; Brendan P. Bradley (Psychopharmacology, 2004)

Minimizing the cost of environmental management decisions by optimizing statistical thresholds - Scott A. Field; Andrew J. Tyre; Niclas Jonzén; Jonathan R. Rhodes; Hugh P. Possingham (Ecology Letters, 2004)
Environmental management decisions are prone to expensive mistakes if they are triggered by hypothesis tests using the conventional Type I error rate ( α ) of 0.05. We derive optimal α ‐levels for decision‐making by minimizing a cost function that specifies the overall cost of monitoring and management. When managing an economically valuable koala population, it shows that a decision based on α = 0.05 carries an expected cost over $5 million greater than the optimal decision. For a species of such value, there is never any benefit in guarding against the spurious detection of declines and therefore management should proceed directly to recovery action. This result holds in most circumstances where the species’ value substantially exceeds its recovery costs. For species of lower economic value, we show that the conventional α ‐level of 0.05 rarely approximates the optimal decision‐making threshold. This analysis supports calls for reversing the statistical ‘burden of proof’ in environmental decision‐making when the cost of Type II errors is relatively high.

Novel microsatellite markers and single nucleotide polymorphisms refine the tylosis with oesophageal cancer ( TOC ) minimal region on 17q25 to 42.5kb: sequencing does not identify the causative gene - Elisabeth J. Huckle; Lynn Rowbottom; Ian Dunham; Joanne E. Langan; Charlotte G. Cole; Joan M. Shaw; John K. Field; Irene M. Leigh; David P. Kelsell; Janet M. Risk; Fiona E. McRonald; Anthony Ellis; et al. (Human Genetics, 2004)

Eye movements to smoking-related cues: effects of nicotine deprivation - Matt Field; Karin Mogg; Brendan P. Bradley (Psychopharmacology, 2004)

Postfire response of North American boreal forest net primary productivity analyzed with satellite observations - Jeffrey A. Hicke; Gregory P. Asner; Eric S. Kasischke; Nancy H. F. French; James T. Randerson; G. James Collatz; Brian J. Stocks; Compton J. Tucker; Sietse O. Los; Christopher B. Field (Global Change Biology, 2003)
Fire is a major disturbance in the boreal forest, and has been shown to release significant amounts of carbon (C) to the atmosphere through combustion. However, less is known about the effects on ecosystems following fire, which include reduced productivity and changes in decomposition in the decade immediately following the disturbance. In this study, we assessed the impact of fire on net primary productivity (NPP) in the North American boreal forest using a 17‐year record of satellite NDVI observations at 8‐ km spatial resolution together with a light‐use efficiency model. We identified 61 fire scars in the satellite observations using digitized fire burn perimeters from a database of large fires. We studied the postfire response of NPP by analyzing the most impacted pixel within each burned area. NPP decreased in the year following the fire by 60–260 g C m −2 yr −1 (30–80%). By comparing pre‐ and postfire observations, we estimated a mean NPP recovery period for boreal forests of about 9 years, with substantial variability among fires. We incorporated this behavior into a carbon cycle model simulation to demonstrate these effects on net ecosystem production. The disturbance resulted in a release of C to the atmosphere during the first 8 years, followed by a small, but long‐lived, sink lasting 150 years. Postfire net emissions were three times as large as from a model run without changing NPP. However, only small differences in the C cycle occurred between runs after 8 years due to the rapid recovery of NPP. We conclude by discussing the effects of fire on the long‐term continental trends in satellite NDVI observed across boreal North America during the 1980s and 1990s.

Satellite estimates of productivity and light use efficiency in United States agriculture, 1982–98 - D. B. Lobell; J. A. Hicke; G. P. Asner; C. B. Field; C. J. Tucker; S. O. Los (Global Change Biology, 2002)
Remote sensing of net primary production (NPP) is a critical tool for assessing spatial and temporal patterns of carbon exchange between the atmosphere and biosphere. However, satellite estimates suffer from a lack of large‐scale field data needed for validation, as well as the need to parameterize plant light‐use efficiencies (LUEs). In this study, we estimated cropland NPP with the Carnegie‐Ames‐Stanford‐Approach (CASA), a biogeochemical model driven by satellite observations, and then compared these results with field estimates based on harvest data from United States Department of Agriculture National Agriculture Statistics Service (NASS) county statistics. Observed interannual variations in NPP over a 17‐year period were well modelled by CASA, with exceptions mainly due to occasional difficulties in estimating NPP from harvest yields. The role of environmental stressors in agriculture was investigated by running CASA with and without temperature and moisture down‐regulators, which are used in the model to simulate climate impacts on plant LUE. In most cases, correlations with NASS data were highest with modelled stresses, while the opposite was true for irrigated and temperature resistant crops. Analysis of the spatial variability in computed LUE revealed significantly higher values for corn than for other crops, suggesting a simple parameterization of LUE for future studies based on the fraction of area with corn. Absolute values of LUE were much lower than those reported in field trials, due to uncommonly high yields in most field trials, as well as overestimates of absorbed radiation in CASA attributed to bias from temporal compositing of satellite data. Total NPP for US croplands, excluding Alaska and Hawaii, was estimated as 0.62 Pg C year −1 , representing ∼20% of total US NPP, and exhibited a positive trend of 3.7 Tg C year −2 . These results have several implications for large‐scale carbon cycle research that are discussed, and are especially relevant for studies of the role of agriculture in the global carbon balance.

Resource Optimization and Symbiotic Nitrogen Fixation - E. B. Rastetter; P. M. Vitousek; C. Field; G. R. Shaver; D. Herbert; G. I. gren (Ecosystems, 2001)

Toward an allocation scheme for global terrestrial carbon models - P. Friedlingstein; G. Joel; C. B. Field; I. Y. Fung (Global Change Biology, 1999)
Summary The distribution of assimilated carbon among the plant parts has a profound effect on plant growth, and at a larger scale, on terrestrial biogeochemistry. Although important progress has been made in modelling photosynthesis, less effort has been spent on understanding the carbon allocation, especially at large spatial scales. Whereas several individual‐level models of plant growth include an allocation scheme, most global terrestrial models still assume constant allocation of net primary production (NPP) among plant parts, without any environmental coupling. Here, we use the CASA biosphere model as a platform for exploring a new global allocation scheme that estimates allocation of photosynthesis products among leaves, stems, and roots depending on resource availability. The philosophy underlying the model is that allocation patterns result from evolved responses that adjust carbon investments to facilitate capture of the most limiting resources, i.e. light, water, and mineral nitrogen. In addition, we allow allocation of NPP to vary in response to changes in atmospheric CO 2 . The relative magnitudes of changes in NPP and resource‐use efficiency control the response of root:shoot allocation. For ambient CO 2 , the model produces realistic changes in above‐ground allocation along productivity gradients. In comparison to the CASA standard estimate using fixed allocation ratios, the new allocation scheme tends to favour root allocation, leading to a 10% lower global biomass. Elevated CO 2 , which alters the balance between growth and available resources, generally leads to reduced water stress and consequently, decreased root:shoot ratio. The major exception is forest ecosystems, where increased nitrogen stress induces a larger root allocation.

Middle pleistocene interglacial sediments at Tye green, Stansted Airport, Essex, England - S. Boreham; M. H. Field; P. L. Gibbard (Journal of Quaternary Science, 1999)

The effects of chamber pressurization on soil‐surface CO 2 flux and the implications for NEE measurements under elevated CO 2 - C. P. Lund; W. J. Riley; L. L. Pierce; C. B. Field (Global Change Biology, 1999)
Soil and ecosystem trace gas fluxes are commonly measured using the dynamic chamber technique. Although the chamber pressure anomalies associated with this method are known to be a source of error, their effects have not been fully characterized. In this study, we use results from soil gas‐exchange experiments and a soil CO 2 transport model to characterize the effects of chamber pressure on soil CO 2 efflux in an annual California grassland. For greater than ambient chamber pressures, experimental data show that soil‐surface CO 2 flux decreases as a nonlinear function of increasing chamber pressure; this decrease is larger for drier soils. In dry soil, a gauge pressure of 0.5 Pa reduced the measured soil CO 2 efflux by roughly 70% relative to the control measurement at ambient pressure. Results from the soil CO 2 transport model show that pressurizing the flux chamber above ambient pressure effectively flushes CO 2 from the soil by generating a downward flow of air through the soil air‐filled pore space. This advective flow of air reduces the CO 2 concentration gradient across the soil–atmosphere interface, resulting in a smaller diffusive flux into the chamber head space. Simulations also show that the reduction in diffusive flux is a function of chamber pressure, soil moisture, soil texture, the depth distribution of soil CO 2 generation, and chamber diameter. These results highlight the need for caution in the interpretation of dynamic chamber trace gas flux measurements. A portion of the frequently observed increase in net ecosystem carbon uptake under elevated CO 2 may be an artifact resulting from the impact of chamber pressurization on soil CO 2 efflux.

Diet quality does not affect resting metabolic rate or body temperatures selected by an herbivorous lizard - K. E. Nussear; R. E. Espinoza; C. M. Gubbins; K. J. Field; J. P. Hayes (Journal of Comparative Physiology B, 1998)

Effect of exercise-induced muscle damage on the blood lactate response to incremental exercise in humans - Michael Gleeson; Andrew K. Blannin; Neil P. Walsh; Christine N. E. Field; Jeanette C. Pritchard (European Journal of Applied Physiology, 1998)

B cell maturation and selection at the marrow-periphery interface - Michael P. Cancro; David M. Allman; Colleen E. Hayes; Vicky M. Lentz; Ryan G. Fields; Alex P. Sah; Mary Tomayko (Immunologic Research, 1998)

Middle Pleistocene temperate deposits at Dingé, Ille-et-Vilaine, northwest France: pollen, plant and insect macrofossil analysis - V. Andrieu; M. H. Field; P. Ponel; J. Guiot; P. Guenet; J.-L. de Beaulieu; M. Reille; M.-T. Morzadec-Kerfourn (Journal of Quaternary Science, 1997)

Modulation of the serological response of specific pathogen-free (EHV-free) foals to EHV-1 by previous infection with EHV-4 or a TK-deletion mutant of EHV-1 - D. Tewari; J. S. Gibson; J. D. Slater; T. O'Neill; D. Hannant; G. P. Allen; H. J. Field (Archives of Virology, 1993)

Alternative products from trees and shrubs to ?The role of trees in sustainable agriculture? conference, Albury, September 30th?October 3rd 1991 - A. Boutland; M. Robinson; J. Field; M. Scheltema; B. Hawkins; P. Bulman; J. Scarvelis; B. Mason; M. Wallace; M. Castley; P. A. Ryan; R. T. Henderson; et al. (Agroforestry Systems, 1992)

BK virus specific IgM responses in cord sera, young children and healthy adults detected by RIA - D. W. G. Brown; S. D. Gardner; P. E. Gibson; A. M. Field (Archives of Virology, 1984)